2015
DOI: 10.3762/bjoc.11.116
|View full text |Cite
|
Sign up to set email alerts
|

Quarternization of 3-azido-1-propyne oligomers obtained by copper(I)-catalyzed azide–alkyne cycloaddition polymerization

Abstract: Summary3-Azido-1-propyne oligomer (oligoAP) samples, prepared by copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) polymerization, were quarternized quantitatively with methyl iodide in sulfolane at 60 °C to obtain soluble oligomers. The conformation of the quarternized oligoAP in dilute DMSO-d 6 solution was examined by pulse-field-gradient spin-echo NMR based on the touched bead model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…101 A first step consisted in the CuAAC polyaddition of 3-azido-1-propyne generated in-situ from the reaction between propargyl bromide and sodium azide. Indeed, the generation of 3-azido-1-propyne in a separate step prior to CuAAC polyaddition would afford an extremely reactive and potentially explosive organic azide (i.e.…”
Section: Tpils Obtained Via Cuaac Polyadditionmentioning
confidence: 99%
“…101 A first step consisted in the CuAAC polyaddition of 3-azido-1-propyne generated in-situ from the reaction between propargyl bromide and sodium azide. Indeed, the generation of 3-azido-1-propyne in a separate step prior to CuAAC polyaddition would afford an extremely reactive and potentially explosive organic azide (i.e.…”
Section: Tpils Obtained Via Cuaac Polyadditionmentioning
confidence: 99%
“…These samples were characterized by SEC and 1 H NMR as can be seen in Figures S1–S3 in the Supporting Information. Our previous work has demonstrated that AP homopolymer is insoluble in all the common solvents examined, including DMF, DMSO, N -methylpyrrolidone (NMP), methanol, acetone, THF, chloroform, and toluene [21,22]. Thus, the solubility of the EG m - b -AP n diblock copolymer samples was examined, and the results are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates that protonation makes the oligomers soluble. The AP oligomer was thus quarternized with methyl iodide to obtain an oligomer soluble in polar organic solvents [22]. Since the quarternized oligomer possesses dense quaternized 1,2,3-triazole moieties, it can be expected to be a precursor of polymeric ionic liquid [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the poor solubility, it was not possible to obtain high-molecular-weight polymers from the AP derivatives by CuAAC polymerization. However, it was possible to obtain dense 1,2,3-triazole oligomers or polymers soluble in common solvents by quaternization of the AP oligomer with methyl iodide [ 34 ] or by connecting to poly(ethylene glycol) (PEG) blocks, i.e., the formation of block copolymers [ 35 , 36 ]. The block copolymers of PEG and dense 1,2,3-triazole blocks form aggregates in water, e.g., spherical micelles and vesicles, depending on the ratio of block lengths, and undergo phase separation at higher temperatures because of cooperative dehydration of the PEG block [ 36 ].…”
Section: Introductionmentioning
confidence: 99%